High-frequency repetitive transcranial magnetic stimulation at dorsolateral prefrontal cortex for migraine prevention: a protocol for a systematic review of controlled trials - Mohamad Safiai, Nabil Izzaatie; Mohamad, Nur Afiqah; Basri, Hamidon; Inche Mat, Liyana Najwa; Hoo, Fan Kee; Abdul Rashid, Anna Misyail; Yusof Khan, Abdul Hanif Khan; Loh, Wei Chao; Baharin, Janudin; Fernandez, Aaron; Samsudin, Intan Nureslyna; Mohamed, Mohd Hazmi; et al. (SAGE Publications, 2022)
Objective: To evaluate the efficacy of high-frequency repetitive transcranial magnetic stimulation over dorsolateral prefrontal cortex as a migraine prevention by conducting a systematic review and meta-analysis. Background: The efficacy of high-frequency repetitive transcranial magnetic stimulation over dorsolateral prefrontal cortex as preventive migraine treatment remains debatable. Methods: PubMed, Scopus, CINAHL, CENTRAL, and BioMed Central databases were searched from their inception until December 2020. Randomised trials comparing high-frequency repetitive transcranial magnetic stimulation over dorsolateral prefrontal cortex with sham for migraine prevention were included. The risk of bias was assessed using the Cochrane guidelines. Headache days, pain intensity, acute medication intake, and disability were extracted as study outcomes and the mean difference with a random-effects model was used to determine the effect size. Results: Meta-analysis revealed that high-frequency repetitive transcranial magnetic stimulation over dorsolateral prefrontal cortex significantly reduced acute medication intake (Mean Difference = 9.78, p = 0.02, 95%CI: 1.60, 17.96, p = 0.02) and functional disability (Mean Difference = 8.00, p < 0.05, 95%CI: 4.21, 11.79). However, no differences were found in headache days and pain intensity reduction, although there was a slight trend favouring high-frequency repetitive transcranial magnetic stimulation. Conclusion: High-frequency repetitive transcranial magnetic stimulation over dorsolateral prefrontal cortex may be effective in reducing acute medication intake and disability. However, more studies are needed to strengthen this preliminary evidence.